Pengelolaan Flight Information Region Di Wilayah Kepulauan Riau Dan Natuna - Mahfud Fahrazi (Fakultas Hukum Universitas Islam Indonesia, 2019)
This article focuses on the study of Flight Information Region (FIR) management in the Riau and Natuna Islands, which since 1946 is still controlled by Singapore. Although various attempts to take over the control have been carried out by the Indonesian government, it is yet to produce any meaningful results. The limitation of the problem in this study is first, the implications that arise from the management of FIR by Singapore on the Riau Islands and Natuna airspace. Second, the efforts that have been made by the Indonesian government to take over the management of FIR by Singapore over the Riau Islands and Natuna airspace. This research uses a normative legal research by analysing the legal issues through international treaties, legal regulations and other literature related to FIR management. The results of the study concluded first, the management of FIR by Singapore over the Riau Islands and Natuna influenced the enforcement of Indonesia's airspace sovereignty and national defence. Secondly, Indonesia's efforts and readiness to take over aviation navigation services include the formation of a special team from several ministries and other relevant institutions to prepare technical and operational steps as well as diplomatic steps in the framework of restructuring the FIR.